2017
DOI: 10.18632/oncotarget.20590
|View full text |Cite
|
Sign up to set email alerts
|

Lunasin functionally enhances LDL uptake via inhibiting PCSK9 and enhancing LDLR expression in vitro and in vivo

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease which regulates serum low-density lipoprotein cholesterol (LDL-C) levels by promoting the degradation of the hepatic low-density lipoprotein receptor (LDLR), and has become an attractive therapeutic target for cholesterol lowering intervention. Lunasin, a 43-amino acid polypeptide initially isolated from soybean, has been previously proven to possess cholesterol lowering activity. Here we identified the down-regulation of PCSK9 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…The presence of the 120 kDa CTF at the cell surface, as evidenced by its ability to be surface biotinylated, is consistent with this assumption. Although pharmacological inhibition or genetic knockdown of BMP1 almost totally inhibited LDLR cleavage, LDLR cell surface expression and LDL uptake were only increased by ~20% suggesting tight regulation of the amount of receptor expressed at the cell surface as observed in previous studies 26,27 .…”
Section: Discussionsupporting
confidence: 66%
“…The presence of the 120 kDa CTF at the cell surface, as evidenced by its ability to be surface biotinylated, is consistent with this assumption. Although pharmacological inhibition or genetic knockdown of BMP1 almost totally inhibited LDLR cleavage, LDLR cell surface expression and LDL uptake were only increased by ~20% suggesting tight regulation of the amount of receptor expressed at the cell surface as observed in previous studies 26,27 .…”
Section: Discussionsupporting
confidence: 66%
“…Lunasin downregulated the expression of genes associated with proprotein convertase subtilisin/kexin type 9 (PCSK9) and upregulated the expression of LDL receptor (LDLR) at the transcriptional and translational levels in HepG2 cells [66]. In ApoE−/− mice, lunasin administration by intraperitoneal injection decreased total cholesterol and LDL-cholesterol levels in the serum by downregulating the expression of PCSK9 and increasing the expression of LDLR and sterol regulatory element-binding protein 2 (SREBP-2) [66]. Soybean glycinin-derived peptides, such as IAVPGEVA, IAVPTGVA, and LPYP, activated the LDLR/SREBP2 pathway in HepG2 cells in vitro, but not in vivo, suggesting that the peptides directly regulate cholesterol metabolism [81].…”
Section: Modulation Of Lipid Metabolismmentioning
confidence: 99%
“…We have previously revealed that lunasin treatment effectively inhibited PCSK9 expression and remarkably elevated LDLR level in hepatocytes and mice [20]; thus, we were prompted to explore whether combination therapy with simvastatin and lunasin could enhance the LDL-C lowering efficacy of simvastatin. In liver tissue, PCSK9 synthesis is largely controlled at the gene transcriptional level by HNF1; there are two members of the HNF1 family, HNF1α and HNF1β.…”
Section: Discussionmentioning
confidence: 99%
“…Lunasin, a 43-amino acid polypeptide with a molecular weight of ~5 kDa, which was initially identified from soybean [16], has been previously proven to possess various pharmacological activities against cancer [17], inflammation [18], and CVD [19]. Interestingly, we previously revealed that lunasin can functionally enhance LDL uptake in hepatocytes via both inhibiting PCSK9 expression and enhancing LDLR level, thereby remarkably reducing total cholesterol (TC) and LDL-C in blood as compared to vehicle control [20]. Thus, in this study, we investigated whether simvastatin combined with lunasin could improve the cholesterol lowering efficacy of simvastatin.…”
Section: Introductionmentioning
confidence: 99%